Cyclizaton of 2´-Hydroxychalcones in Dimethyl Sulphoxide - Kumar, Surender; Makrandi, J.K. (Asian Journal of Chemistry, 2016)
An attempt to cyclize 2-Hydroxy-chalcones in dimethyl sulphoxide (DMSO) has been made.